Neurosurgical management of epidural abscess after traumatic brain injury: a case report - Lizarraga Valderrama, Héctor Mijail (2024)
Cranioencephalic trauma is an event caused by force on the container that holds the brain content, which causes inertia to cause acceleration and deceleration injuries, producing hemorrhages and/or fractures; These can generate a series of complications such as epidural abscess which, being very close to the brain, constitutes an emergency for its management and follow-up15. On this occasion we show the case of a patient with epidural abscess caused by cranioencephalic trauma and neurosurgical management.